Analysis of The Impact of Traffic and Pedestrianization Environment in Malioboro - Ahmad Munawar; Budi Kamulyan (Journal of the Civil Engineering Forum, 2021)
The phenomenon of the increasing number of Malioboro tourists is known to be raising traffic problems in the area, annually. These problems ranges from congestion and increased vehicle exhaust emissions, to increasing side friction. This has placed pressure on the Yogyakarta city government, as they have been tasked to plan and improve traffic management, through the transformation of Malioboro into a pedestrianized area. Moreover, pedestrianization in urban centres has been widely practiced in big cities of various countries. This application also has an impact on the significant changes in traffic flow on roads, around the area. This study simulated a traffic flow scenario on roads around Malioboro, via the use of a VISSIM software, in order to determine the saturation level of the movement, as well as the resulting emissions. The collection of generation and attraction data were carried out through household interview or traffic surveys, around the research area. However, the data used were obtained from the traffic survey results. The VISSIM is known to be a Microscopic flow simulation software, which is often used for traffic models. In this simulation, the existing condition, i.e, the Malioboro road that was still opened for motorized vehicles, was compared with the area's scenario (closed from motorized vehicle), as well as several gyratory alternatives on the surrounding. In order to determine the emission data released due to transportation activities, a node was placed at several simulated intersections. Also, three alternatives were observed to have been compared, with recommendations stating that those having less traffic impacts should be used.